The Role of the Digital Economy in Enhancing Economic Development in Iraq: A Strategic Analysis of Transformation Opportunities and Challenges - Khalid Ahmed Khalid, Aveen (Journal of Economics and Administrative Sciences, 2025)
This study examines the role of the digital economy in enhancing economic development in Iraq, focusing on the period from 2003 to 2022. Utilizing an Autoregressive Distributed Lag (ARDL) model, the research analyzes the relationship between GDP growth and key digital economy indicators, including the E-Government Development Index (EGDI), E-Participation Index (EPI), Online Service Index (OSI), Telecommunication Infrastructure Index (TII), and Internet Usage (UI). Data were sourced from the World Bank, International Telecommunication Union (ITU), and United Nations E-Government Survey. The ARDL model, selected based on the Akaike Information Criterion (AIC), was employed to capture both short-term dynamics and long-term equilibrium relationships. Diagnostic tests, including Augmented Dickey-Fuller (ADF), Phillips-Perron (PP), Toda-Yamamoto causality, and cointegration tests, were conducted to ensure model robustness. The findings reveal significant positive relationships between GDP growth and digital economy indicators, particularly EGDI and UI, highlighting the importance of e-government development and internet penetration in driving economic growth. However, EPI and TII showed negative long-term impacts, suggesting structural and institutional challenges. The study concludes that targeted investments in digital infrastructure, regulatory reforms, and capacity-building initiatives are essential for leveraging digital transformation to achieve sustainable economic development in Iraq. Policymakers are advised to prioritize digital inclusion and innovation to reduce oil dependency and foster economic resilience.